A The impact of Islamic finance on the structure of stock returns of a diversified sample of indices: The impact of Islamic finance on the structure of stock returns of a diversified sample of indices - flifel, kaouther (Archives of Business Research, 2019)
Whether they are Muslim or not, investors interested in the stock market indices wonder about the performance of their investments. This study attempts to provide some answers to guide the decision process. This is of practical interest especially with the development of financial products in which Islamic market indices are the underlyings. In general, we study the impact of Islamic Finance on the structure of stock returns of a diversified sample of indices. Data were collected over a period of 11 years (January 2004 to December 2014). The results show the interest brings the use of such indices.